Chlorophyll fluorescence analysis for assessing water deficit and Arbuscular Mycorrhizal Fungi (AMF) inoculation in cassava (Manihot esculenta Crantz) - Oyetunji, O.; Ekanayake, I.J.; Osonubi, O. (2007)
Arbucsular Mycorrhizal Fungi (AMF) are implicated as phyto-stimulators of various physiological processes of its symbiotic plants. The influences of AM fungi and water deficit on quantum yield of photochemistry (Fv/Fm) of photo-system II of cassava leaves were therefore investigated. Field experiment was conducted at Ajibode village while the semi-controlled experiment was conducted at the International Institute of Tropical Agriculture (IITA), Ibadan, Nigeria. One improved cassava clone (TMS 4(2) 1425) and a landrace (TME1) were investigated. The soil is Oxic Paleustalf in both fields and controlled experiments. The controlled experiments were arranged factorially in a complete randomized design, while the field experiment was a randomized complete block design. The plants were adequately watered at alternate days. After two months, one half of the plants in each treatment were subjected to water stress. All treatments were replicated three times. Results obtained from chlorophyll fluorescence probe indicated that inoculated AM fungi enhanced photochemical efficiency of light reactions of the photosystem II (PS II) in intact cassava leaf tissues both under irrigation and water stress conditions. Water deficit levels based on more negative leaf had adverse effects on chlorophyll fluorescence of both genotypes. However, the adverse effect of water stress was significantly reduced by AM inoculation. Fv/Fm values could be a potentially useful criterion in selecting for drought tolerance and AM fungi efficiency of cassava.